Perkembangan Luas Areal dan Produksi Sawit serta Pengaruhnya Terhadap PDRB Sub Sektor Perkebunan Propinsi Bengkulu - Rita Feni; Edy Marwan (Hasanuddin University, 2023)
Palm is one of commodity from plantation sub sector that largely planted by farmer in Bengkulu Province. Plantation area and production of palm oil keep increasing year by year in Bengkulu, this shows that farmer interest in planting palm is quiet high moreover it is considered as profitable commodity among farmer. This study aims to (1) getting know the development of plantation area and productivity of palm oil in Bengkulu year by year (2) getting know the effect of plantation area and productivity of palm towards Plantation PDRB subsector in Bengkulu. This study used quantitative method. By characteristic this study is statistic descriptive. Data used in this study is secondary data. Analysis done by using trend and multiple linear regression. The study result shows that PDRB development, plantation area and production of palm oil from 2009 to 2019 tend to increase. Plantation area and production of palm oil together affect Plantation PDBR Sub sector significantly but have no effect partially towards Plantation PDBR Sub sector.